Masliy I. A. Cooperation G. F. Kvitky-Osnovyanenko with the magazine «Sovremennyk» - Masliy I. A. (Philological Treatises, 2020)
The article deals with the analysis of the history of publications G. F. Kvitka in the magazine "Sovremennyk". The problem of reception of works written in Russian in criticism 1830-1840's are considered. Special attention is paid to epistolary heritage of the writer.